A Comparative Study between “The Algerian My Book of English and The British Junior Textbook for Grade 1” - Meriem BENOUARETH (My University, 2023)
ABSTRACT Textbooks play a vital role in education, serving as structured resources that guide teaching and learning processes. This study undertakes a comparative examination of the Algerian “My Book of English” textbook and “the UK English Junior textbook for grade 1”, aiming to shed light on their shared attributes and distinctive features. Employing a mixed-method design, the study collected qualitative and quantitative data through an eclectic checklist for textbook analysis and a questionnaire targeting third-year primary school EFL teachers. The research sample consists of 25 third-year primary school EFL teachers from various schools in Souk Ahras during the academic year 2022-2023. The participants were selected randomly from sixty-nine primary schools. In addition to the questionnaire, a checklist was employed to analyze both textbooks comprehensively. The findings unveiled that both textbooks prioritize the development of the four language skills, comprehensive grammar coverage, and shared instructional approaches that underscore interaction and learner-centeredness. These textbooks also meet young learners' needs by providing age-appropriate content. Contrasts emerged between the two textbooks, particularly in terms of visual appeal, where the UK English textbook showcased high-quality images compared to the Algerian textbook. Furthermore, disparities encompassed structural elements, length, unit organization, and activity types. The Algerian textbook distinguished itself by offering a range of activities compared to the UK English textbook's approach. In summary, this comparative study contributes to understanding the role of textbooks in EFL instruction, highlighting their strengths and differences. The insights gained from this research can be of a great help for textbook designer as well as primary school EFL teacher. Therefore, it can inform curriculum design and teaching strategies, for the ultimate aim of enriching language education in primary schools. ------------------------------------------- الملخص تلعب الكتب المدرسية دورًا حيويًا في التعليم، حيث تعتبر مصادر منظمة توجه عملية التدريس والتعلم. تقوم هذه الدراسة بفحص مقارن لكتاب "كتابي في اللغة الإنجليزية" الجزائري وكتاب اللغة الإنجليزية البريطاني للصف الأول، بهدف تسليط الضوء على السمات المشتركة والمميزة فيهما. تتألف عينة البحث من 25 معلمًا لمادة اللغة الإنجليزية كلغة أجنبية في السنة الثالثة من المدرسة الابتدائية من مدارس مختلفة في سوق أهراس خلال العام الدراسي 2022-2023. تم اختيار المشاركين بشكل عشوائي من بين تسعة وستين مدرسة ابتدائية. باستخدام تصميم طريقة مختلطة، جمعت الدراسة بيانات نوعية وكمية من خلال استبيان يستهدف معلمي اللغة الإنجليزية كلغة أجنبية في السنة الثالثة من المدرسة الابتدائية. بالإضافة إلى ذلك، تم استخدام قائمة تدقيق لتقييم الكتب المدرسية بشمولية. كشفت النتائج أن الكتابين يعطيان الأولوية لتنمية مهارات اللغة الأربع، وتغطية شاملة للقواعد، وأساليب تدريس مشتركة تؤكد على التفاعل وتحويل المتعلم إلى محور العملية التعليمية. تقدم هذه الكتب أيضًا لاحتياجات الصغار بمحتوى مناسب للعمر. ظهرت تباينات بين الكتابين، خاصة فيما يتعلق بالجاذبية البصرية، حيث عرض كتاب اللغة الإنجليزية البريطاني صورًا عالية الجودة بالمقارنة مع الكتاب الجزائري. وعلاوة على ذلك، اشتملت الاختلافات على العناصر البنيوية، والطول، وتنظيم الوحدات، وأنواع الأنشطة. تميز الكتاب الجزائري نفسه من خلال تقديم مجموعة من الأنشطة مقارنة بالنهج الذي اتبعه كتاب اللغة الإنجليزية البريطاني. في ملخص، تساهم هذه الدراسة المقارنة في فهم دور الكتب المدرسية في تدريس اللغة الإنجليزية كلغة أجنبية، مسلطة الضوء على نقاط القوة والاختلافات فيها. يمكن أن تؤثر النظرات التي تم الحصول عليها من هذا البحث على تصميم المناهج واستراتيجيات التدريس، مثرية التعليم اللغوي في المدارس الابتدائية ----------------------------